Identification of palatine rugae in forensic odontology in the indonesian population: a scoping review - Saputri, Ikra Yuni; Suhardjo, Suhardjo; Fauzi, Hilman; Oscandar, Fahmi (Universitas Padjadjaran, 2025)
Introduction: The study of palatine rugae in forensic odontology has become increasingly vital as a means of identifying individuals, particularly in scenarios where conventional identification methods prove inadequate. This scoping review focuses on the identification of palatine rugae in the Indonesian population. Method: A scoping review was conducted using the Arksey and O'Malley framework and PRISMA-ScR guidelines. Relevant articles were sourced from PubMed, ScienceDirect, and Google Scholar using Boolean operators and relevant keywords. Studies were included if they involved Indonesian populations, used palatal rugae for identification, were original research, published in Indonesian or English, and available in full text between March 2014 and March 2024. We excluded review articles, non-human studies, and papers in other languages. Two independent reviewers screened and selected articles. Results: The results of the scoping review identified various classifications of palatine rugae, with three articles using the Thomas and Kotze method and one article each using the Kapali, Trobo, Lysell, and Carrea methods. Two articles studied rugae inheritance, and one examined post-orthodontic stability. The widely used Thomas and Kotze method focuses on the length, shape, and direction of the rugae but has limitations in sex determination. Additionally, the Trobo, Kapali, Lysell, and Carrea classifications are also used due to their simplicity and clarity. This study investigated the pattern of palatine rugae and found that the pattern remains consistent before and after orthodontic treatment and is inherited from parent to child. The study also identified potential language bias, limited Indonesian literature on palatine rugae, and methodological variations across research articles. Conclusion: This scoping review affirms the reliability of palatine rugae in forensic odontology in Indonesia, highlights the need for further research to enhance understanding of rugae patterns and inheritance mechanisms, and contributes to the knowledge base for future forensic research and investigations.